The Relationship between Corruption and the Shadow Economy in Ukraine and Other Central and Eastern European Countries - Cherviakova, Valentyna; Cherviakova, Tetiana (Comparative Economic Research. Central and Eastern Europe, 2020)
The article investigates the causes, essence, and peculiarities of corruption and the shadow economy, as well as how they are related, in Ukraine in comparison with other Central and Eastern European countries. A correlation‑regression analysis of statistical data revealed a direct correlation connection of different strengths and statistical significance between levels of corruption and the shadow economy in all Central and Eastern European countries. However, the degree to which corruption impacts the variation in the levels of the shadow economy differs significantly in countries across the region. The key conclusion is that in countries with relatively high levels of corruption and the shadow economy, corruption causes a smaller share of the shadow economy than in countries with relatively low levels of these phenomena. Causes of the weak correlation between levels of corruption and the shadow economy in Ukraine were identified. The main corruption and non‑corruption factors of Ukraine’s economy shadowing were determined. It was concluded that policy and measures to counteract corruption and the shadow economy in Ukraine should be aimed at eliminating their root causes rather than manifestations.